2017
DOI: 10.1016/j.supflu.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

A cooling and two-step depressurization foaming approach for the preparation of modified HDPE foam with complex cellular structure

Abstract: This article reports on the fabrication of modified high-density polyethylene (HDPE) foams with complex cellular structure (CCS) using supercritical CO 2 as a physical blowing agent by a cooling and two-step depressurization method. HDPE was modified by dicumyl peroxide (DCP) and carbon nanotubes (CNTs) to improve its viscoelasticity and foaming behavior. The gel content test demonstrated that the cross-linking structure formed in the modified HDPE samples. Compared with that of neat HDPE, the viscoelasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…When the Δ P 1 was 0 and 1 MPa, MCS occurred in all the CPBS foams with similar average cell size of about 30–50 μm and similar cell density of about 6.5 × 10 7 –1.95 × 10 8 cells cm −3 . This indicated that there was no cell nucleation in the cooling stage and the first depressurization stage . The MCS generated and formed in the second depressurization stage.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…When the Δ P 1 was 0 and 1 MPa, MCS occurred in all the CPBS foams with similar average cell size of about 30–50 μm and similar cell density of about 6.5 × 10 7 –1.95 × 10 8 cells cm −3 . This indicated that there was no cell nucleation in the cooling stage and the first depressurization stage . The MCS generated and formed in the second depressurization stage.…”
Section: Resultsmentioning
confidence: 94%
“…The melting temperature ( T m ) and crystallization temperature ( T c ) of polymer are two important indicators to the setting of the saturation temperature ( T s ) and foaming temperature ( T f ) during the foaming process . In general, T s should be higher than T m , in order to ensure that the polymer was fully melted and the blowing agent could be dissolved into the polymer melt completely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase in PE‐ g ‐GMA content, the χ c of various PBS samples kept almost unchanged (Table ), which should be ascribed to two aspects. On the one hand, the branching points in PBS/PE‐ g ‐GMA samples could be acted as the heterogeneous nucleation sites, which could promote PBS crystallization nucleation . On the other hand, the movement of molecular chains of various PBS samples into the crystal lattice was restricted by the existence of branching and/or micro crosslinking structures in PBS, which was adverse to its crystallization growth …”
Section: Resultsmentioning
confidence: 99%
“…Then the insoluble parts were dried at 80 °C for 6 h to remove the residual chloroform. According to the following equation, the gel fraction of various PBS samples was calculated and each sample was measured for three times: Gel0.25emfraction=W0Wg×100% where W g and W 0 represented the weights of the initial PBS sample and dried insoluble part of sample, respectively.…”
Section: Methodsmentioning
confidence: 99%